The biosemiotics of Aldo Leopold - Rebecca C. Potter (Sign Systems Studies, 2016)
Responding to Jean-Claude Gens’ article, “Uexküll’s Kompositionslehre and Leopold’s ‘land ethic’ in dialogue”, which appeared in Sign Systems Studies in 2013, the article further develops a direct connection between Aldo Leopold’s approach to ecology and Jakob von Uexküll’s umwelt theory. The connection between Uexküll and Leopold is especially evident in Leopold’s descriptions of animal behaviour that he presents in the first part of his seminal work, A Sand County Almanac. In this work specifically, Leopold illustrates the biosemiotic processes described by Uexküll, and does so with a purpose: to reshape our understanding of the biotic community as a place of semiotic interaction.